2016
DOI: 10.1108/aeat-02-2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model ensemble wake vortex prediction

Abstract: Tag der mündlichen Prüfung: 25.07.2017 Diese Dissertation ist auf den Internetseiten der Universitätsbibliothek online verfügbar. Für meinen Großvater. v Eidesstattliche Erklärung Ich versichere hiermit an Eides Statt, dass ich die vorliegende Dissertation mit dem Titel "Multi-Model Ensemble Wake Vortex Prediction" selbstständig und ohne unzulässige fremde Hilfe erbracht habe. Ich habe keine anderen als die angegebenen Quellen und Hilfsmittel benutzt. Für den Fall, dass die Arbeit zusätzlich auf einem Datenträ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 126 publications
(364 reference statements)
0
6
0
Order By: Relevance
“…Please note that, unlike in previous sections, the standard deviation used for defining 2σ bounds is not based on any specific distribution. Sensitivity analysis conducted in the previous studies has shown good convergence property of the method [46]. Figure 9 shows the MCS results for a single WakeMUC landing.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Please note that, unlike in previous sections, the standard deviation used for defining 2σ bounds is not based on any specific distribution. Sensitivity analysis conducted in the previous studies has shown good convergence property of the method [46]. Figure 9 shows the MCS results for a single WakeMUC landing.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In this case, the vortices are assumed to be further advected by the wind while staying at constant altitude. Although the models' sensitivities to the ambient conditions differ, it has been found in a previous study [39] that no so-called expert models exist. They are defined as models that show significantly better performance than the other models for a distinct meteorological parameter interval.…”
Section: Multimodel Ensemble Methods and Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study [15] the evaluation of suitable MME methods demonstrated that the ensemble approach can indeed improve wake vortex forecasts. The Bayesian Model Averaging [16] turned out to achieve better results for our application while being more robust than the Reliability Ensemble Averaging [17,18] and is thus chosen to be further refined. Compared to Monte-Carlo Simulations the probabilistic BMA-forecast could reach a much higher reliability in reproducing the vortices measured by lidar as demonstrated in Körner et al [19].…”
Section: Introductionmentioning
confidence: 97%